Meaning-centered education : international perspectives and explorations in higher education - Kovbasyuk, Olga.; Blessinger, Patrick (New York : Routledge, 2013)
"In a time of globally changing environments and economic challenges, many institutions of higher education are attempting to reform by promoting standardization approaches. Meaning-Centered Education explores the counter-tide for an alternative vision of education, where students and instructors engage in open meaning-making processes and self-organizing educational practices. In one contributed volume, Meaning-Centered Education provides a comprehensive introduction to current scholarship and pedagogical practice on meaning-centered education. International contributors explore how modern educational scholars and practitioners all around the world are implementing a comprehensive framework that supports meaning making in a classroom. This edited collection is a valuable resource for higher education faculty and scholars interested in renewing the deep purposes of higher education"--
pt. I. Theory and principles of meaning-centered education -- pt. II. Worldwide successful practices : voices of experience -- pt. III. Enhancing meaning-centered teaching and learning.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Education, Higher -- Philosophy; Inquiry-based learning; Electronic books